การพัฒนาแบบประเมินสมรรถนะพยาบาลออร์โธปิดิกส์ โรงพยาบาลสังกัดกระทรวงกลาโหม - อัจฉรา สุขมาก (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
The purposes of this study were to develop and to set standard of orthopaedic nurses competency scale for hospitals of the Ministry of Defense. The samples from 4 hospitals of the Ministry of Defense were 94 orthopaedic nurses consisted of 14 orthopaedic experts included nursing administrators, nurse educators and clinical nurses specialist, who participated in constructin the competency assessment form. The 89 consisted of head nurses and staff nurses who used the competency assessment form. Thestandard score was set by 5 othropaedic expert nurses from hospitals of the Ministry of Defense. The assessment form was behaviorally anchored rating scale: BARS 4 point scales. The results were as follow: 1. The orthopaedic nurses competency scale for hospitals of the Ministry of Defense consisted of 7 competencies with 23 items. The 7 competencies were 1) orthopaedic nursing, 2) risk management, 3) health promotion and rehabilitation, 4) orthopaedic instrument technique, 5) communication and coordination, 6) leadership and management and 7) education and otheopaedic nursing research. 2. The quality of instrument were content validity index (CVI) was .93 and tested of reliability by method of interrater reliability was .82. 3. The arithmetic mean of competency assessed by head nurse was 2.44 which in the moderate level. 4. The standard score of orthopaedic nurses competency scale in the hospitals of the Ministry of Defense was 2.26. The orthopaedic nurses competency scale in the hospitals of the Ministry of Defense = .17 (orthopaedic nursing) + .16 (risk management) + .15 (health promotion and rehabilitation) + .15 (orthopaedic instrument technique) + .15 (communication and coordination) + .12 (leadership and management) + .10 (education and orthopaedic nursing research)